Effect of providing free glasses on children's educational outcomes in China: cluster randomized controlled trial. (23rd September 2014) - Ma, Xiaochen; Zhou, Zhongqiang; Yi, Hongmei; Pang, Xiaopeng; Shi, Yaojiang; Chen, Qianyun; Meltzer, Mirjam E; le Cessie, Saskia; He, Mingguang; Rozelle, Scott; Liu, Yizhi; Congdon, Nathan
Abstract : Objective To assess the effect of provision of free glasses on academic performance in rural Chinese children with myopia. Design Cluster randomized, investigator masked, controlled trial. Setting 252 primary schools in two prefectures in western China, 2012-13. Participants 3177 of 19 934 children in fourth and fifth grades (mean age 10.5 years) with visual acuity <6/12 in either eye without glasses correctable to >6/12 with glasses. 3052 (96.0%) completed the study. Interventions Children were randomized by school (84 schools per arm) to one of three interventions at the beginning of the school year: prescription for glasses only (control group), vouchers for free glasses at a local facility, or free glasses provided in class. Main outcome measures Spectacle wear at endline examination and end of year score on a specially designed mathematics test, adjusted for baseline score and expressed in standard deviations. Results Among 3177 eligible children, 1036 (32.6%) were randomized to control, 988 (31.1%) to vouchers, and 1153 (36.3%) to free glasses in class. All eligible children would benefit from glasses, but only 15% wore them at baseline. At closeout glasses wear was 41% (observed) and 68% (self reported) in the free glasses group, and 26% (observed) and 37% (self reported) in the controls. Effect on test score was 0.11 SD (95% confidence interval 0.01 to 0.21) when the free glasses group was compared with the control group. The adjusted effect of providing free glasses (0.10, 0.002 to 0.19) was greater than parental education (0.03, −0.04 to 0.09) or family wealth (0.01, −0.06 to 0.08). This difference between groups was significant, but was smaller than the prespecified 0.20 SD difference that the study was powered to detect. Conclusions The provision of free glasses to Chinese children with myopia improves children's performance on mathematics testing to a statistically significant degree, despite imperfect compliance, although the observed difference between groups was smaller than the study was originally designed to detect. Myopia is common and rarely corrected in this setting. Trial Registration Current Controlled Trials ISRCTN03252665 .